Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbasis TPACK terhadap Hasil Belajar Peserta Didik Kelas IV pada Mata Pelajaran IPAS SD Negeri 01 Munggur - Adella Gita Praviesta; Oktiana Handini; Mukhlis Mustofa (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study aims to determine the significant effect of the Problem Based Learning (PBL) based on the Magnet TPACK of SD Negeri 01 Munggur. This research uses a qualitative type of research based on the philosophy of polytheism. The population and sample used for the research were 28 students of class IV of SD Negeri 01 Munggur. The technique used in selecting the sample was purposive sampling. This research utilizes the One-Group Pretest-Posttest Design. In this design, before the treatment is given, a pre-test (alwall test) is given before the treatment is given and after the treatment is given, a post-test (final test) is given. Data collection techniques using observation, tests and documentation. Based on the results of the study, the conclusion is that there is a significant use of the Problem Balsed Lealing model of learning based on TPACK in class IV of SD N 01 Munggur. The effect of the PBL learning model based on TPACK on the learning outcomes of IPALS in class IV before the treatment was given, the maximum score was 90, while the minimum score was 45. The mean score was 63.92, the median was 62.5. Data analysis results using palired salmpel t-tes it is known that the mean value it is known that the mean pretest value of students 57,6 while the mean posttest for students was 63.92. The results of the statistical test with the crossed sample t-test recognize the effect of the Problem Balsed Learning (PBL) model based on TPACK Regarding the learning outcomes of grade IV students in the subject of science at SD Negeri 01 Munggur, it was found that based on the paired sample t-test table, the significant value (2 tallies) 0.000 <0.05 indicated that there was a difference between the initial and final variables(pretest & posttest), this proves that there is a significant effect on the difference in the need for calcualn given for the variable.